Upaya Penanganan Dampak Negatif dan Penyebarluasan Berita Hoaks di SMAN 36 Jakarta - Aulia Masruroh; Fatwa Patimah Nursa’adah; Rita Kusumawardhani (Jurnal Ragam Pengabdian, 2025)
The spread of hoaxes among students has become a serious issue in the digital era, particularly due to the low level of digital literacy among adolescents. This community service activity aimed to raise awareness among students of SMAN 36 Jakarta about the dangers of hoaxes through education and digital literacy training. The methods used in this program included socialization, interactive discussions, and the creation of digital campaigns in the form of posters and educational videos by the students. The results showed that students became more critical in receiving and sharing information, as well as more capable of identifying characteristics of hoaxes. However, challenges such as uneven student participation and limited digital access were still encountered. Therefore, follow-up programs, parental involvement, and school policies are needed to support the development of a sustainable digital literacy culture. This activity proves that an educational approach based on digital literacy can serve as a preventive solution to hoax dissemination within the school environment.